1991
DOI: 10.1111/j.1469-8137.1991.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the pigments, carbohydrates and growth of red spruce as affected by exposure to ozone for two growing seasons

Abstract: SUMMARYThree-year-old red spruce seedlings were exposed to various concentrations of ozone, from 0-4 to 3 times ambient, for two consecutive growing seasons in open-top chambers in Ithaca, NY, USA, Exposures, which varied with changes in daylength, were from 30 May to 14 December 1987 and 1 June to 1 December 1988, Seedling biomass, foliar pigments and carbohydrate content of roots and shoots were assessed once or twice per month. Tree biomass increased through the summer and declined slightly in late autumn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 33 publications
1
19
2
Order By: Relevance
“…Winter hardiness was reduced . However, reductions of chlorophyll were not observed Amundson et al, 1991) or were much smaller (20%) than in the current field study (50°o)-Needle losses have also not been reported as a consequence of ozone exposure. Thus, the contribution of ozone, as single agent, to the observed damage symptoms remains unclear.…”
Section: Seasonal and Age-related Changes Of Nutrients In Needles Frocontrasting
confidence: 82%
See 1 more Smart Citation
“…Winter hardiness was reduced . However, reductions of chlorophyll were not observed Amundson et al, 1991) or were much smaller (20%) than in the current field study (50°o)-Needle losses have also not been reported as a consequence of ozone exposure. Thus, the contribution of ozone, as single agent, to the observed damage symptoms remains unclear.…”
Section: Seasonal and Age-related Changes Of Nutrients In Needles Frocontrasting
confidence: 82%
“…In coniferous Amundson et al, 1991). Norway spruce trees species symptoms of injury are characterized by exposed to enhanced ozone (addition of about 30 nl needle discolouration and needle losses.…”
mentioning
confidence: 99%
“…The ability of seedlings, and probably mature trees, to compensate photosynthetically for lost foliage may help reduce the impact, but because older trees have a much smaller proportion of their foliage in the youngest age class, compensation may be much less effective in mature trees (Amundson et al, 1991). In California's Mediterranean-type climate, soil dries progressively through the summer (Barbour & Major, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Stress may promote the formation of harmful reactive oxygen species (ROS) which have the capacity to initiate chlorophyll bleaching, lipid peroxidation, protein oxidation, and injury to nucleic acids (Kangasjarvi et al, 2005). The effect of CO 2 and O 3 on plant growth and productivity has been determined separately for a large number of plant species, but very little work has focused on their interactive effect 2,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies on combination effects of CO 2 with temperature, moisture 6,7 and effects of O 3 with SO 2 or NO 2 8,9 on plant have been reported. Interactive effects of CO 2 and O 3 on winter wheat 10 , potato 11,12 , aspen and birch 13 .…”
Section: Introductionmentioning
confidence: 99%